Prevalence of Mental Disorders in Patients With Chronic Thromboembolic Pulmonary Hypertension - Dering, Madelaine-Rachel; Lepsy, Nicole; Fuge, Jan; Meltendorf, Tanja; Hoeper, Marius M.; Heitland, Ivo; Kamp, Jan C.; Park, Da-Hee; Richter, Manuel J.; Gall, Henning; Ghofrani, Hossein A.; Ellermeier, Dietmar; et al. (Frontiers in Psychiatry, 2022)
Objective: Pulmonary hypertension (PH) is a chronic and progressive pulmonary vascular disease resulting in symptoms such as shortness of breath and fatigue and leading to death from right heart failure if not adequately treated. Chronic thromboembolic pulmonary hypertension (CTEPH) is a subgroup of PH characterized by obstruction or occlusion of pulmonary arteries by post-embolic fibrotic material. To date, few studies examined symptoms of depression and anxiety in patients with CTEPH, showing depression levels as high as 37.5%. However, none of the former studies used structured expert interviews. Methods: Mental disorders were diagnosed using the Structured Clinical Interview for DSM-5. Prevalences of mental disorders in patients with CTEPH were compared to prevalences in patients with pulmonary arterial hypertension (PAH) and the general German population. Quality of life (QoL) was measured with WHO Quality of Life questionnaire (short form). Factors associated with QoL were analyzed with linear regression and the diagnostic value of the Hospital Anxiety and Depression Scale (HADS) was evaluated using receiver operating characteristics curve analysis. Results: 107 patients with CTEPH were included. Almost one third of the patients (31.8%) had current psychological disorders. Panic disorder (8.4%), specific phobia (8.4%) and major depressive disorder (6.5%) were the most prevalent mental illnesses. The prevalence of panic disorders was higher in CTEPH compared to the German population while major depressive disorder was fewer in CTEPH compared to PAH. The presence of mental disorders had a major impact on QoL. HADS discriminated depression and panic disorder reliably. Conclusion: Mental disorders are common in patients with CTEPH and associated with an impaired QoL. The HADS may be a useful screening tool for panic and depression disorders in patients with CTEPH. Further research on therapeutic strategies targeting mental disorders in patients with CTEPH is needed.